Identification of nonstructural type traps within the limits of northern side of Dnieper-Donets Depression according to the data of AVO analysis and seismic inversion - І.Л. Михалевич; П.М. Кузьменко; А.П. Тищенко; А.С. Вижва; С.А. Вижва (Геофизический журнал, 2021)
Nonstructural type traps in the sedimentary cover of the northern side of the Dnieper-Donets depression are poorly studied by seismic methods due to many factors among which are the following: complicated geological structure and not so high quality of given data of geological-geophysical studies of last years. Identification of lithologically screened gas-saturated object has been demonstrated based on the studies of elastic dynamic characteristics by the methods of AVO-analysis and elastic seismic inversion. Acoustic and elastic properties have been analyzed in the wells with cross-dipole real and synthesized acoustics. Gas-saturated intervals have been identified based on the ratios VP /VS and acoustic impedance. According to AVO-studies within the northern side of DDD in the stratum of productive horizons of the moscovian horizon a positive answer has been obtained to the question «if AVO analysis works correctly in general within the limits of the northern side of DDD deposits». Determining factors that influence on the result during the application of AVO-analysis at the most part of gas condensate field of the northern side of DDD are effective thicknesses, depths of occurrence, lithology, poro-sity and quality of given seismic data and data from geophysical surveys of wells. Taking into account minor effective thicknesses, small values of porosity, significant depths of occurrence of productive layers typical for the northern side of DDD, the majority of gas-saturated intervals are not at all identified in the wave field by dynamic characteristics of seismic signal. All the seismic anomalies analyzed had effective thicknesses from 6 to 20 m. Within the limits of deposits of the northern side of DDD, AVO-anomalies of the 2nd class are modeled. Along with positive experience of identification of dynamically cont-rasting objects in the wave field limitations to use methods of AVO-analysis and elastic seismic inversion are generalized for the northern side shown in particular and the whole Dnieper-Donets depression.